ANALISIS KELAYAKAN BISNIS PENAMBAHAN INDUK IKAN NILA NIRWANA PADA POKDAKAN MINA NILA SARI PURWAKARTA - Muhammad Ridho Muhaimin; Andan Hamdani (University of Jember, 2021)
Mina Nila Sari Aquaculture Group is an aquaculture group at Legoksari Village, Purwakarta District. Pokdakan Mina Nila Sari have 30 members. Hatchery unit conditions with 43 broodfish packages can not fulfill the larvae demand yet. The purpose of this study was to formulate business development idea addition of broodfish Nirwana tilapia for larvae fulfillment at Mina Nila Sari Purwakarta Aquaculture Group and to analyze the feasibility of this business development study on marketing aspects, production aspects, organization and management aspects, collaboration aspects as non-financial sub aspect and to analysis financial aspect by using Incremental Net Benefit to determine incremental benefit on development business. In terms of analyzing the finansial aspect will be using investment criteria namely Net Present Value, Internal Rate of Return, Net Benefit-Cost Ratio and Payback Period. The result of this study shows business development study addition of broodfish Nirwana tilapia for larvae fulfillment at Mina Nila Sari Purwakarta Aquaculture Group is feasible to “Go”. Calculation of Incremental Net Benefit shows this development business is profitable.